DAMPAK POLA PENGEMBANGAN DIRI TERHADAP KEMANDIRIAN DAN PRESTASI BELAJAR ANAK - Aep Saepuloh (Jurnal Eksplorasi Bimbingan dan Konseling, 2019)
Development activities in an effort to form students' character and personality through counseling services related to personal and social issues, learning activities, and career development, as well as extra-curricular activities. The author of this study conducted on Foster Children Foundation Manarussalam Cirebon using quantitative descriptive method. The sample in this study amounted to 20 foster children from a population of 50 children with probability sampling non-sampling technique. Research shows that the majority of self-development patterns have developed, which is about 52% or 0.52 where the figure stands at 0.40 to 0.59, which means the pattern of selfdevelopment of children is high enough. Furthermore, for some aspects of well-developed independence that is around 54% or 0.54 where the number is from 0.40 to 0.59, which means the development of children is high enough. The ability of learning achievement, most of it has not been developed.